Morphometric and meristic characteristic study of pora pora fish (Mystacoleuseus padangensis) caught in the Lower Bah Bolon River, Simalungun Regency - Yunita Sri Malem Barus; Suri Purnama Febri; Andika Putriningtias; Edwarsyah Edwarsyah (Acta Aquatica: Aquatic Sciences Journal, 2026)
This study aims to examine the morphometric and meristic characteristics of pora-pora fish (Mystacoleucus padangensis) found downstream of the Bah Bolon River, Simalungun. Sampling was carried out from April to June 2024 with a total of 58 fish. Measurement results showed that the length of the pora-pora fish ranged from 12 - 17 cm, with a weight range of 25 - 69 g. From the morphometric and meristic measurements, it can be concluded that the growth pattern of pora-pora fish is positively allometric (b>3) with a regression coefficient (b) of 3.4945 and a coefficient of determination (R²) of 0.9246, which means that the increase in fish weight is faster than the increase in body length. The condition factor of pora-pora fish in the Bah Bolon River was found to range from 0.7 - 1.23, categorized as lean and underweight fish. Keywords: Bah Bolon River; Morphometric; Meristic; Pora-pora fish